Primary Central Nervous System T-Cell Lymphoma of the Brain in an Immunocompetent Patient - Mat Nor, Khariah; Marlina Tanty Ramli Hamid; Norizal Mohd Noor; Hazman Mohd Nor; Kalai Arasu Muthusamy; Looi Lai Meng (Journal Of Cardiovascular, Neurovascular & Stroke, 2023)
PRIMARY CENTRAL NERVOUS SYSTEM T- CELL LYMPHOMA OF THE BRAIN IN AN IMMUNOCOMPETENT PATIENT Primary central nervous system (PCNS) T-cell lymphoma is a rare disease and rarer if it is seen in immunocompetent patients. The PCNS lymphoma makes up 1-7% of primary brain tumors. PCNS T-cell lymphoma accounts for about 2% of all PCNS lymphoma and almost 99% are seen in immunocompromised patients (Latta et al 2010, Batchelor et al 2003). Here, we report a case of PCNS T-cell lymphoma in an elderly patient who is immunocompetent. The radiological findings, histopathological studies, and reviews of the current literature of this rare condition are discussed.